PENGARUH KOSENTRASI DAUN KELADI TERHADAP BIOKOMPOSIT FOAM TAPIOKA DAN KITOSAN - Putra, Ferdi Prayoga; Harsojuwono, Bambang Admadi; Arnata, I Wayan (Program Studi Agroteknologi, Fakultas Sains dan Teknologi, Universitas Muhammadiyah Siddenreng Rappang, 2025)
Biocomposite foam offers an environmentally friendly solution to replace synthetic polymer-based packaging that is difficult to degrade. This study aimed to investigate the effect of taro leaf powder (Colocasia esculenta (L.) Schott) concentration on the characteristics of tapioca-and chitosan-based biocomposite foam, as well as to determine the optimal concentration for producing the best-performing foam. The research employed a Randomized Block Design (RBD) with five levels of taro leaf powder concentration: 1%, 1.5%, 2%, 2.5% and 3%, tested across four blocks based on biocomposite foam production time. The observed variables included tensile strength, tear strength, density, elongation at break, compression set, thickness, swelling, and biodegradation. Data were analyzed using ANOVA followed by the Least Significant Difference (LSD) test. The results showed that variations in taro leaf powder concentration produced the best foam properties, with a tensile strength of 2.04 N/cm2, tear strength of 1.46 N/cm2, density of 0.22 g/mL, elongation at break of 2.77%, compression set of 17.28%, thickness of 12.78 mm, swelling of 0.84%, and a biodegradation time of 15.75 days.